Dexamethasone-loaded cochlear implants: How to provide a desired "burst release" - A. Qnouch; V. Solarczyk; J. Verin; G. Tourrel; P. Stahl; F. Danede; J.F. Willart; P.E. Lemesre; C. Vincent; J. Siepmann; F. Siepmann (Elsevier, 2021)
Cochlear implants containing iridium platinum electrodes are used to transmit electrical signals into the inner ear of patients suffering from severe or profound deafness without valuable benefit from conventional hearing aids. However, their placement is invasive and can cause trauma as well as local inflammation, harming remaining hair cells or other inner ear cells. As foreign bodies, the implants also induce fibrosis, resulting in a less efficient conduction of the electrical signals and, thus, potentially decreased system performance. To overcome these obstacles, dexamethasone has recently been embedded in this type of implants: into the silicone matrices separating the metal electrodes (to avoid short circuits). It has been shown that the resulting drug release can be controlled over several years. Importantly, the dexamethasone does not only act against the immediate consequences of trauma, inflammation and fibrosis, it can also be expected to be beneficial for remaining hair cells in the long term. However, the reported amounts of drug released at "early" time points (during the first days/weeks) are relatively low and the in vivo efficacy in animal models was reported to be non-optimal. The aim of this study was to increase the initial "burst release" from the implants, adding a freely water-soluble salt of a phosphate ester of dexamethasone. The idea was to facilitate water penetration into the highly hydrophobic system and, thus, to promote drug dissolution and diffusion. This approach was efficient: Adding up to 10% dexamethasone sodium phosphate to the silicone matrices substantially increased the resulting drug release rate at early time points. This can be expected to improve drug action and implant functionality. But at elevated dexamethasone sodium phosphate loadings device swelling became important. Since the cochlea is a tiny and sensitive organ, a potential increase in implant dimensions over time must be limited. Hence, a balance has to be found between drug release and implant swelling.